Transcription activation by GC-boxes: evaluation of kinetic and equilibrium contributions. - Yean, D (1996)
Basal and GC-box activated transcription were compared by various assays in order to learn the basis for an 8-fold difference observed under standard conditions. The time required for forming pre-initiation complexes and initiating and elongating RNA synthesis, and the extent of transcription reinitiation were found to be quite similar for basal and activated transcription, with complex formation being the slow step in both cases. The extent of activation was found to vary widely with the amount of template DNA used. Activated pre-initiation complexes were found to have a higher stability than basal complexes. The data are interpreted to indicate that GC-box elements do not stimulate the rate constants for critical steps in this system but rather increase the equilibrium constant for pre-initiation complex formation, probably by 10-30-fold.